In Vitro Callus induction Gurmar (Gymnema Sylvestre, R.Br) for Secondary Metabolite Synthesis - Gholba Niranjan Dilip (Department of Plantation Crops and Spices, College of Horticulture, 2000)
Diabetes mellitus is a disorder affecting 100 million people round the globe. Gymnema sylvestre R.Br. is being used in antidiabetic therapies with good success. Depletion of forest area has reduced the supply of Gymnema leaves. To bridge the gap between an ever increasing demand and the dwindling supply of antidiabetic medicines from Gymnema, this study was undertaken to examine whether these metabolites could be produced by in vitro techniques. This study was undertaken at the Department of Plantation Crops and Spices, College of Horticulture, Kerala Agricultural University, Vellanikkara during May, 1998 to November, 1999. Callus cultures were initiated in test tubes and were maintained at 26 ± 2 QC temperature and 60 to 80 per cent relative humidity for three months. Observations on growth of calli were noted at weekly intervals, while saponin production was noted after each month. Internode, node, petiole, leaf lamina and root segments were evaluated as explants to initiate calli. Among them, internode and petiole were found to have maximum potential to initiate and proliferate calli. Root explants did not produce significant amounts of callus. The auxins evaluated for stimulating callus production were 2,4-D, NAA, lAA and .IBA. Among them, 2,4-D was the most potent in callusing followed by NAA. Both, lAA and IBA performed very poorly. The cytokinins (BA and kinetin) showed statistically similar performances. The combination of2,4-D with BA produced maximum callus. MS medium supplemented with 2, 4-D (2 mg rl) and BA (I mg rl) was selected as the basal medium due to high callusing and high saponin yields. Stress inducing chemicals were added to it to examine whether they increased the production of saponins. It was found that addition of mannitol, activated charcoal, peptone and malt extract enhanced the